Performance analysis of SSK modulation for UAVs communication - Tastan, Mustafa Cihan; Ilhan, Haci (ELSEVIER, 2021)
In this paper, we investigate the performance of Space Shift Keying (SSK) modulation on a Multiple-Input-Multiple-Output (MIMO) wireless communication system for Unmanned Aerial Vehicles (UAVs) over Rician fading channels. SSK modulation can be a key technique for energy-efficient and reliable communication scenarios for UAV applications. The first part of the performance analysis consists of theoretical derivations for the Bit Error Rate (BER) performance of UAVs' SSK communication. The second part consists of theoretical derivations for the outage probability. Error rate performance comparison between SSK modulation for UAV communication systems and conventional systems is given. Then, the proposed system's diversity order is derived and presented as a number of receive antenna N-r. The BER performance decrease against non-line-of-sight channel scenarios is shown via simulation results due to the line-of-sight effect on the SSK modulated system. Monte Carlo simulations validate theoretical derivation results for various transmit - receive antennas and Rician K factor values. (C) 2021 Elsevier Inc. All rights reserved.
Keywords: Space shift keying (SSK) modulation; Unmanned aerial vehicles (UAVs); Bit error rate (BER); Outage probability; Air-to-air (A2A); Ground-to-air (G2A); AERIAL VEHICLES UAVS; CIVIL APPLICATIONS; MIMO; MODEL; Telecommunications; Transportation